Aurelian a męczennicy - Suski, Robert (Vox Patrum, 2007)
The persecution of Christians was stopped after capture of Valerian in June 260. During the forty-three years from 260 to 303 the Christian Church had a relatively comfortable conditions to growth. According to Eusebius of Ceasarea and Lactantius the emperor Aurelian (270-275) wanted to renew the persecution in the last few months of his reign. The emperor was assassinated by a conspiracy of his higher officers and he didn’t realize this plans. We have several accounts of martyrdoms which took place under Aurelian in Italy, Asia Minor, Palestine, Dalmatia and Gaul. The reliability of many of this martyrdoms is doubled. Some of this martyrs were genuine, but they hadn’t been punished during the rule of Aurelian. For example Felix was executed either rule of Valerian or Aurelian. Sometimes authors of acts of martyr confused Aurelian with Marcus Aurelius. The following names of martyrs are fictious. The dates of the martyrdoms don’t fit to chronology for thè end of Aurelian’s rule.